Development of Fe3O4/Ag core/shell-based multifunctional immunomagnetic nanoparticles for isolation and detection of CD34+ stem cells. Issue 3 (4th May 2018) - Quynh, Luu Manh; Dung, Chu Tien; Mai, Bach Thi; Huy, Hoang Van; Loc, Nguyen Quang; Hoa, Nguyen Quang; Thach, Pham Tuan; Anh, Bui Viet; Thao, Chu Thi; Nam, Nguyen Hoang; Nhung, Hoang Thi My; Long, Nguyen Ngoc; et al.
ABSTRACT: Fe3 O4 /Ag core/shell nanoparticles functionalized with the free amino (NH2 ) functional groups (Fe3 O4 /Ag-NH2 ) were conjugated with fluorescent electron coupled dye (ECD)-antiCD34 antibody using the 1-ethyl-3-(3′-dimethyl-aminopropyl) carbodiimide (EDC) catalyst (ECD – Electron Coupled Dye or R Phycoerythrin-Texas Red is a fluorescent organic dye attached to the antibody). The characteristic fluorescence of ECD in the antibody was investigated and was used as a good indicator for estimating the percentage of the antibodies that were successfully conjugated with the nanoparticles. The conjugation efficiency was found to increase depending on the V NP : V AB ratio, where V NP and V AB are the volumes of the nanoparticle solution (concentration of 50 ppm) and the as-purchased antibody solution, respectively. The conjugation efficiency rapidly increased from approximately 18% to approximately 70% when V NP : V AB was increased from 2:1 to 100:1, and it gradually reached the saturated state at an efficiency of 95%, as the V NP : V AB was equal to 300:1. The bioactivity of the abovementioned conjugation product (denoted by Fe3 O4 /Ag-antiCD34) was evaluated in an experiment for the collection of stem cells from bone marrow samples.